Macaco guigó (Callicebus coimbrai) : dispersão de sementes e conhecimento ecológico na Mata Atlântica de Sergipe - Baião, Sirley Almeida Adelino (2013)
The study presented here is a component of the Guigó Project , a long-term conservation-oriented investigation of the ecology of the titi monkeys of the Brazilian state of Sergipe. Here, the primary objective was to provide detailed data on the role of C. coimbrai as a frugivore and seed disperser, its contribution to the functioning of the ecosystem, and the understanding of this role held by local residents. Callicebus coimbrai groups were monitored between April and October, 2012, at two sites Sergipe the Fazenda Trapsa in the municipality of Itaporanga D Ajuda, and the Mata do Junco Wildlife Refuge in Capela. Data were collected through the continuous monitoring of the two study groups, when each of the group s visits to a fruiting tree was documented (time of day, duration of feeding bout, number of individuals, number of fruits ingested) and mapped with a GPS. All observed defecation events were also documented (time, individual, presence of copraphagous insects) and whenever possible a sample of the faeces was collected for analysis. Both groups fed on fruit throughout the study period, although the Junco group was far more frugivorous, overall, than the Trapsa group in terms of both time spent feeding and the number of fruit patches visited each month. A total of 31 plant species were exploited for their fruit at the two sites, although only two were common to both sites (Jaccard index = 0.065). Overall, faeces samples were collected from 61.9% of observed defecation events. However, only 27.3% of these samples contained seeds, although there was a considerable difference between groups (14.3% for Trapsa and 47.9% for Junco), which reflected the inter-site difference in feeding behaviour (there was a significant correlation between the number of feeding patches visited each month and the number of samples containing seeds). Seeds of up to three species and 14 seeds were found in any given sample. An analysis of dispersal distances indicated a mean gut passage rate of 4 hours and 44 minutes for Trapsa group, with a mean distance of 189.7 m, whereas for Junco group, mean passage time was only 2 hours 51 minutes, and mean distance, 126.0 m. The results indicate that C. coimbrai is an important agent of seed dispersal in the Atlantic Forest of Sergipe. Scarabid beetles of the genus Canthidium (Eucanthidium) were observed or captured in all months of the study period, and may be important secondary dispersers of the seeds defecated by the titis. Interviews with local residents at both sites indicated that most people know the forest and its fauna, but very few had any reliable knowledge on the ecology of C. coimbrai. Important differences were also recorded between sites in the knowledge and opinions of the residents. Overall, the results of the study emphasise the importance of C. coimbrai as a frugivore and seed disperser, as well as the need to understand temporal and spatial variation in the ecology of the species in order to guarantee long-term conservation strategies. A greater knowledge of the ecology of the species also appears to have great potential for the development of integrated programs of environmental education